HubunganKecerdasan Intrapersonal DenganKepercayaanDiriPadaMahasiswaAngkatan 2013 Program Studi PG PAUD FKIP Universitas Riau - Sidabutar, Fitriayu Sidabutar; Indarto, Wusono Indarto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The study aims at determining the relationship of intrapersonal intelligence and confidence of 2013 academic year students of PG ECD FKIP UR. The population of the study was the students of 2013 academic year consisting of 84 people. Since the population of the study was less than 100, total sampling technique was applied to draw the sample of the study. The technique of collecting data was standardized tests concerning information about various aspects of a person who generates a quantitative description of the aspects studied. The results of the testing hypothesis of a simple correlation analysis (r) obtained intrapersonal intelligence correlation and the confidence of students (r) is 0.423 with a probability value of 0.000, therefore the probability is <0.05 (0.000 <0.05). It implies that Ho is rejected. The results show that there is a fairly strong correlation between intrapersonal intelligence and self-confidence of students. While the direction of the relationship is positive because the value of r is positive, it means that the higher the intrapersonal intelligence, the higher the confidence of students. The coefficient of determination is generated equal to r2 = 17.89 where p = 0.000 (p <0.05), it can be seen that the influence of intrapersonal intelligence 17.89% of the student self-confidence. It is concluded that there is a positive correlation between intrapersonal intelligence and confidence of the students. Keywords: Intrapersonal Intelligence, Self Confidence